The denial of moral dilemmas as a regulative ideal. Issue 2 (3rd March 2016) - Cholbi, Michael
Abstract: The traditional debate about moral dilemmas concerns whether there are circumstances in which an agent is subject to two obligations that cannot both be fulfilled. Realists maintain there are. Irrealists deny this. Here I defend an alternative, methodologically-oriented position wherein the denial of genuine moral dilemmas functions as a regulative ideal for moral deliberation and practice. That is, moral inquiry and deliberation operate on the implicit assumption that there are no genuine moral dilemmas. This view is superior to both realism and irrealism in accounting for moral residue and other crucial phenomenological dimensions of our experience of moral dilemmas.